2022
DOI: 10.1161/circulationaha.120.045373
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Prevents Hypercholesterolemia by Suppressing 12α-Hydroxylated Bile Acids

Abstract: Background: The risk of cardiovascular disease in type 1 diabetes remains extremely high, despite marked advances in blood glucose control and even the widespread use of cholesterol synthesis inhibitors. Thus, a deeper understanding of insulin regulation of cholesterol metabolism, and its disruption in type 1 diabetes, could reveal better treatment strategies. Methods: To define the mechanisms by which insulin controls plasma cholesterol levels, we kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 94 publications
(151 reference statements)
0
16
0
Order By: Relevance
“…In addition, spearman correlation coefficient analysis showed that the genus Escherichia-Shigella was positively correlated with LDL and LA, and negatively correlated with TBA. A new study showed that bile acid could promote intestinal cholesterol absorption and suppress hepatic cholesterol synthesis to prevent hypercholesterolemia (Semova et al, 2022). High levels of LDL are recognized as one of the risk factors leading to the occurrence and development of coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, spearman correlation coefficient analysis showed that the genus Escherichia-Shigella was positively correlated with LDL and LA, and negatively correlated with TBA. A new study showed that bile acid could promote intestinal cholesterol absorption and suppress hepatic cholesterol synthesis to prevent hypercholesterolemia (Semova et al, 2022). High levels of LDL are recognized as one of the risk factors leading to the occurrence and development of coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…50,77 A recent study demonstrated that hepatic insulin receptors also play a role in preventing intestinal cholesterol absorption. 78 This effect of hepatic insulin receptors was due to suppression of 12α-hydroxylated bile acid production 78 mediated by suppression of the transcription factor FoxO1. 79 Thus, silencing of the enzyme Cyp8b1, which generates 12α-hydroxylated bile acid, prevented hypercholesterolemia in mice with hepatic deletion of the insulin receptor and in a mouse model of T1D.…”
Section: Growing Evidence For Beneficial Effects Of Insulin On Athero...mentioning
confidence: 99%
“…As expected, ezetimibe ameliorated these parameters in this cohort of patients. 2 From a clinical perspective, macrovascular disease continues to be a major burden for patients with diabetes, and cholesterol-lowering therapy has been shown to decrease both events and mortality. 13 It is important to note that although most prospective evidence derives from studies in patients with type 2 diabetes, small clinical trials and observational evidence support the efficacy and safety of cholesterol-lowering therapy in patients with T1D.…”
Section: Article See P 969mentioning
confidence: 99%
“…In the intestine, increased CA/CDCA ratio favors cholesterol absorption, which ultimately leads to higher circulating low-density lipoprotein cholesterol and increased atherosclerosis risk. The findings of Semova et al 2 are highlighted in blue. IR indicates insulin resistance.…”
mentioning
confidence: 94%
See 1 more Smart Citation